2015
DOI: 10.2147/clep.s83839
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported body mass index among middle-aged participants in the Norwegian Women and Cancer study

Abstract: BackgroundBody mass index (BMI) based on self-reported height and weight has been criticized as being biased because of an observed tendency for overweight and obese people to overestimate height and underestimate weight, resulting in higher misclassification for these groups. We examined the validity of BMI based on self-reported values in a sample of Norwegian women aged 44–64 years.MethodsThe study sample of 1,837 participants in the Norwegian Women and Cancer study self-reported height and weight, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 27 publications
4
74
0
1
Order By: Relevance
“…47 There was, however, a small but statistically significant under-reporting of weight, which would affect self-reported BMI; this tendency was largest among overweight and obese women. 20,47 A survey of the PA levels in the adult population in Norway showed that 34% of women reached the national guidelines for PA. 48 This proportion is higher than in our study. The relatively large number of cases made it possible to investigate subtypes of endometrial cancer, however the proportion of type 2 endometrial cancer was too low to allow for separate analyses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…47 There was, however, a small but statistically significant under-reporting of weight, which would affect self-reported BMI; this tendency was largest among overweight and obese women. 20,47 A survey of the PA levels in the adult population in Norway showed that 34% of women reached the national guidelines for PA. 48 This proportion is higher than in our study. The relatively large number of cases made it possible to investigate subtypes of endometrial cancer, however the proportion of type 2 endometrial cancer was too low to allow for separate analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Self‐reported BMI has been validated for the NOWAC study, indicating that there was a substantial agreement between self‐reported and measured BMI values . There was, however, a small but statistically significant under‐reporting of weight, which would affect self‐reported BMI; this tendency was largest among overweight and obese women . A survey of the PA levels in the adult population in Norway showed that 34% of women reached the national guidelines for PA .…”
Section: Discussionmentioning
confidence: 99%
“…Height and weight were self-reported, and there is a well-established tendency to underestimate height and weight, which increases with age and BMI [33]. A validation study of BMI in NOWAC was recently conducted and showed substantial agreement between self-reports and objective measurements values, although greater misclassification due to underreporting was observed in women with overweight and obesity [34]. Further, the physical activity scale in NOWAC was recently validated against a sensor that monitored heart rate and movement, showing a significant agreement but only moderate Spearman's rank correlation coefficients (0.36-0.46, p < 0.001) [35].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer rates are the same in our cohort as in the general population of the same age [19] and the prevalence of obesity in this paper is slightly lower than that of the general population (10%, 2012) [45]. Also, as mentioned above, the diet questions have been validated, as has the question on physical activity [26], diabetes [21] and BMI [27], and the results are in the same range as those found in other cohorts. Also, only one question was asked regarding preparation methods of potatoes to the women in the NOWAC study, but as shown above, this is the preferred preparation method in this age group.…”
Section: Discussionmentioning
confidence: 99%